Methane fermentation of chicken manure at mesophilic conditions - Zhadan, Sergiy; Shapovalov, Yevhenii; Patrick, Ngogang; Salyuk, Anatoly; Yakymenko, Igor (My University, 2015)
Poultry is one of the most intensive and mechanized agricultural sectors. Poultrymanure is the main ecological problem of poultry farms and its poor management can cause seriousenvironmental damage. As far as birds absorb energy of plant feed badly and that more than half ofthe energy is used unproductively – it goes to the manure, it can be seen as a powerful source ofrenewable energy. Methane digestion is an effective method of animal waste processing. Poultry manure has a higher fraction of biodegradable organic matter than other livestock wastes. The aim of our study was to investigate methanogenesis of chicken manure in a wide range of moisture content values in the mesophilic mode.
Keywords: кафедра харчової хімії; біогаз; biogas; метанова ферментація; methane fermentation; курячий послід; chiken manure